Microsimulation - a survey of methods and applications for analyzing economic and social policy - Joachim Merz (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1994)
This essential dimensions of microsimulation as an instrument to analyze and forecast the individual impacts of alternative economic and social policy measures are surveyed in this study. The basic principles of microsimulation, which is a tool for practical policy advising as well as for research and teaching, are pointed out and the static and dynamic (cross-section and life-cycle) approaches are compared to one another. Present and past developments of microsimulation models and their areas of application are reviewed, focusing on the US, Europe and Australia. Based on general requirements and components of microsimulation models a microsimulation model's actual working mechanism are discussed by a concrete example: the concept and realization of MICSIM, a PC microsimulation model based on a relational database system, an offspring of the Sfb 3 Statitic Microsimulation Model. Common issues of microsimulation modeling are regarded: micro/macro link, behavioural response and the important question of evaluating microsimulation results. The concluding remarks accentuate the increasing use of microcomputers for microsimulation models also for teaching purposes. – – Die essentiellen Dimensionen der Mikrosimulation als ein Instrument zur Analyse und Prognose individueller Wirkungen ökonomischer und sozialpolitischer Politikalternativen werden in dieser Studie übersichtsweise behandelt. Die Prinzipien der Mikrosimulation, die ein Werkzeug der praktischen Politikberatung als auch der Forschung und Lehre ist, werden herausgearbeitet und statische und dynamische (Querschnitts- und Lebenszyklus-) Ansätze miteinander verglichen. Heutige und vergangene Entwicklungen von Mikrosimulationsmodellen und ihre Anwendungsbereiche werden mit Schwerpunkt auf die Vereinigten Staaten, Europa und Australien beschrieben. Auf der Basis genereller Anforderungen und Komponenten von Mikrosimulationsmodellen werden die Mechanismen von Mikrosimulationsmodellen an einem konkreten Beispiel diskutiert: dem Konzept und der Realisation von MICSIM, einem PC Mikrosimulationsmodell auf der Basis eines relationalen Datenbanksystems, eine Weiterentwicklung des Statischen Sfb 3 Mikrosimulationsmodells. Gemeinsame Merkmale der Modellierung von Mikrosimulationsmodellen werden betrachtet: Mikro/Makro-Verknüpfung, Verhaltensreaktionen und die wichtige Frage der Bewertung von Mikrosimulationsergebnissen. Die abschließenden Bemerkungen akzentuieren die zunehmende Verwendung von Mikrosimulationsmodellen auch in der Lehre.
Keywords: C80; C81; D10; D30; D31; J20; 330; Microsimulation; Microanalytic Simulation Models; Microanalysis; Economic and Social Policy Analysis; Mikrosimulation; Mikroanalytische Simulationsmodelle; Mikroanalyse; Wirtschafts- und sozialpolitische Politikanalyse